Community Empowerment of Nagari Salimpek in Developing a Herbal Cosmetic Village Based on Family Medicinal Plants (TOGA) - Yenny, Satya Wydya; Gustia, Rina; Rahmatini; Usman, Elly; Asri, Ennesta; Akhyar, Gardenia; Ariani, Tutty; Sari, Mutia; Sari, Indah Indria; Yossy, Vesri; Julia, Dwi Sabtika; Ashar, Miranda; Taria, Sari Almira (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Nagari Salimpek in Alahan Panjang, West Sumatra, has a potential for wellness tourism due to its rich biodiversity, especially medicinal and cosmetic plants. However, community awareness in managing Family Medicinal Gardens (TOGA) remain limited, with only three of twenty household groups actively cultivating herbal plants. This condition emphasizes the need for community empowerment to optimize health and economic benefits from local resources. This community service program aimed to enhance local capacity in cultivating and processing TOGA as the basis for developing a Herbal Cosmetic Village. The programme began on 19 July 2025 and was evaluated over six months. Activities included educational sessions on TOGA utilization, training on herbal and cosmetic plant processing, distribution and planting of herbal seeds, and the signing of a Memorandum of Agreement (MoA) with local stakeholders. A pre-test and post-test evaluation involving 31 participants showed significant improvement in knowledge, with understanding of the “herbal center village” concept rising from 29% to 55% and awareness of Nagari Salimpek’s potential increasing from 32% to 77%. Overall, participants gained broader insights into the role of TOGA in health, cosmetics, and economic development. These results highlight the importance of continued education, mentorship, and government support to establish Nagari Salimpek as a model Herbal Cosmetic Village for wellness tourism.